Exploring Callout and Cancel Culture: Impacts on Sensitivity and Ethical Responsibility in Digital Spaces among Generation Z (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
IntroductionThe emergence of callout and cancel culture initially represented a form of positive activism, demanding accountability during a pivotal shift in power dynamics, especially concerning individuals amassing significant influence. These cultures involve publicly criticizing individuals, brands, and celebrities for their transgressions, occasionally resulting in boycotts and exclusion from social circles. With the surge of interactive social media platforms, these practices gained momentum, inevitably raising questions about their effects on sensitivity and morality. As such, this study aims to explore the relationship between callout and cancel culture, sensitivity, and ethical responsibility among Generation Z members in digital spaces. MethodologyThe research employed a descriptive design, targeting Filipino Generation Z participants aged 16-25, regardless of their educational and residential backgrounds. Data was gathered using a validated questionnaire, and the respondents' profiles were described using frequency and percentage counts. To analyze the extent of awareness and participation, weighted mean was utilized. The study employed the Chi-Square test to explore relationships between gender, religious affiliations, type of school, cultural ethnicity, and social media exposure, cancel-callout awareness, and practice. Pearson's Product Moment Correlation was used to assess relationships between age, social roles, family educational background, and the variables. Results and DiscussionThe study revealed that respondents displayed moderate social media exposure and an intermediate level of awareness about callout and cancel culture. However, actual engagement in these practices was relatively low. Notably, gender roles significantly influenced social media exposure, although this connection was not observed with callout and cancel culture. Other profile variables presented mixed or inconclusive relationships with social media exposure and awareness/practice of callout and cancel culture. Increased awareness regarding these cultures correlated with heightened participation. Conclusion and RecommendationsIn conclusion, the research highlights the intricate relationships between callout and cancel culture, sensitivity, and morality among Generation Z individuals in digital spaces. To foster responsible participation in these cultures, the study recommends the development and validation of an educational forum. Moreover, replication and further investigation of this phenomenon's broader implications on shaping social consciousness are encouraged. Ultimately, adopting an educational forum on callout and cancel awareness stands as a practical step forward in cultivating sensitivity and morality among Generation Z members in digital realms. Furthermore, expanding research to encompass different dimensions of the phenomenon is essential for a comprehensive understanding and addressing its potential effects on social awareness.
Keywords: call out culture; cancel culture; social consciousness